Efeitos dos compostos de selênio e zinco nas lesões gastrointestinais induzidas por etanol em ratos - Ineu, Rafael Porto (2012)
Gastric ulcer is a world widespread illness that affectes a great number of people and it is correlated to life style, food intake, alcohol and smoke in association or not to stress behavior. The lesions are in association with oxygen reactive species (ROS) production. It is been know that some elements, selenium and zinc, shows great effect scavenger in detoxification of ROS production, avoiding many damages caused by ROS. Based on these considerations, the present study intend to investigate the effect of oral administration of diphenyl diselenide (PhSe)2 and zinc chloride (ZnCl2) in an experimental model of gastric lesion induced by oral administration of ethanol 70% in rats and, particularly the involvement of oxidative stress. For this propose we measured TBARS production, reactive species (RS) levels, ascorbic acid content, total e non-protein thiol groups, superoxide dismutase (SOD) and catalase (CAT) activities from stomach and intestine of rats exposed to ethanol additionally, damage in tissues were measure by micro and macroscopic histopathology analyses. The model of gastrointestinal lesions induced by ethanol is widely used by many authors because it is a model that causes various changes in gastric tissue, exacerbated ROS formation, imbalance in antioxidant defenses and modification of the activity of several enzymes involved in ROS detoxification. In this study, oral ethanol 70% was administered in rats to cause gastric lesions and to enhance oxidative stress. Stomach´s micro and macroscopic analyses showed that (PhSe)2 at low doses (0.01 and 1.0 mg/kg) protected and reverted gastric lesions and attenuated the oxidation alterations caused by ethanol. Similar results could be verified when ZnCl2 (27 mg/kg) was administered orally. ZnCl2 demonstrated to be efficient in to protect and reverse the injuries against gastrointestinal damage caused by ethanol. These elements restored the biochemical parameters to normal values. Macroscopic analyses revealed that both elements, selenium and zinc, could protect and re-epithelialize the stomach. Pre- and post-treatment with (PhSe)2 showed benefic effects against lipid peroxidation measured by TBARS production, wich diminished, even as an enhancement of ascorbic acid content and stomach SOD activity when compared to ethanol. It was also verified for ZnCl2 (27 mg/kg), an ability to protect and to reverse against gastrointestinal damages caused by ethanol, even though this element was able to restore biochemical parameters to control values. Macroscopic analyses showed that ZnCl2 had positive results in prevent and re-epithelialize the mucosa against lesions. ZnCl2 significantly protected and reversed gastrointestinal TBARS and RS production that were enhanced by ethanol as well as prevented and reversed for total SH groups. However, ZnCl2 only protected the diminished in gastrointestinal ascorbic acid content and prevented and restored the decreased of stomach and intestine CAT activity. Therefore, this study is a promising field to development of new drugs and new therapies and also can take to a better understanding of mechanism of action involved in the gastric antioxidant process, even though to enhance the research about elements effects in gastrointestinal ulcers.